Forgotten and lost? Archival research of aerial photographic collections of the Western Front 1914-1918: A guide to the archives - Stichelbaut, Birger (Prostor, kraj, čas, 2015)
Historical aerial photographs are an often overlooked source of information for archaeological, historical and landscape research. This monograph provides an overview and introduction to the collections which found their origin in the First World War and which are amongst the earliest systematic aerial collections. Along the Western Front from the end of 1915 onwards, aerial photo-reconnaissance units were sent out to record the outline of the enemy's defences. The photographs were produced by an almost industrial process, brought together over four years, and survive in large quantities~archival collections are spread out across Europe, the United States and even Australia. The most important and interesting collections are discussed and dealt with, with a focus on their content, quantity, and geographic distribution.